Evidence from the Skilled-Unskilled Canadian Wage Index - Devoretz, D.J.; Reed, Clyde (Relations industrielles / Industrial Relations, 1984)
The authors critically reassess the standard view that Canada's skilled-unskilled wage differential has collapsed over the past four decades.